(untitled) (Konturen, 2020)
Brecht’s so-called anti-war drama Mother Courage and her Children (1939) will be read as a migration drama that demystifies rhetorical cynicism as a coping device for the traumatic torments of migration. By placing Brecht’s work in the context of Peter Sloterdijk’s theory of cynicism, our reading demonstrates how this work adds further perspectives to Thomas Nail’s recent theory of migration and to the discussion of the play’s theatrical production.